Antimicrobial peptide temporin derivatives inhibit biofilm formation and virulence factor expression of Streptococcus mutans - Jiang, Shangjun; Zha, Yanmei; Zhao, Ting; Jin, Xiao; Zhu, Ruiying; Wei, Shuangshuang; Wang, Rong; Song, Yanting; Li, Lushuang; Lyu, Junchen; Hu, Wenting; Zhang, Daqi; et al. (Frontiers in Microbiology, 2023)
Temporin-GHa obtained from the frog Hylarana guentheri showed bactericidal efficacy against Streptococcus mutans. To enhance its antibacterial activity, the derived peptides GHaR and GHa11R were designed, and their antibacterial performance, antibiofilm efficacy and potential in the inhibition of dental caries were evaluated. Bacterial survival assay, fluorescent staining assay and transmission electron microscopy observation were applied to explore how the peptides inhibited and killed S. mutans. The antibiofilm efficacy was assayed by examining exopolysaccharide (EPS) and lactic acid production, bacterial adhesion and cell surface hydrophobicity. The gene expression level of virulence factors of S. mutans was detected by qRT-PCR. Finally, the impact of the peptides on the caries induced ability of S. mutans was measured using a rat caries model. The results shown that the peptides inhibited biofilm rapid accumulation by weakening the initial adhesion of S. mutans and reducing the production of EPS. Meanwhile, they also decreased bacterial acidogenicity and aciduricity, and ultimately prevented caries development in vivo.GHaR and GHa11R might be promising candidates for controlling S. mutans infections.